Coal–rock damage characteristics caused by blasting within a reverse fault and its resultant effects on coal and gas outburst - Kui Gao (Nature Portfolio, 2021)
Abstract In view of the coal and gas outburst accidents occur frequently caused by blasting in geological structural belt, in order to study the mechanical characteristics of coal rock in tectonic belt disturbance by blasting and blasting vibration effect influenced on the stability of surrounding rock, coal–rock damage and failure characteristics within a reverse fault caused by a blasting stress wave were investigated using numerical analyses and experiments. According to the experimental results, the causes of coal and gas outburst dynamic disasters within a reverse fault during blasting are analyzed. The outcomes indicated that the crushing circle created by the crack propagation near the blasting hole severely damaged the fault plane and floor rocks adjacent to the footwall of the reverse fault. Fractures also extended to the upper and lower coal seams of the reverse fault; this caused the surface of the coal seam to fall off and severe internal damage. According to theoretical analysis, the reflection of the blasting stress wave propagating to the reverse fault intensified the damage to coal and rock. Elastic strain energy accumulation within the reverse fault structural zone was accompanied by high-stress concentration. The reverse fault tectonic region was destroyed by blasting vibration. It increased gas pressure and caused a weak surface, which provided a channel for gas flow and a dynamic basis for the occurrence of coal and gas outburst. The research results have important theoretical value to reveal the mechanism of coal and gas outburst in tectonic belt induced by blasting.